2023
DOI: 10.1007/s10522-023-10018-1
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the role of l-lactate as a signaling molecule in skin aging

Abstract: Abstractl-lactate is a catabolite from the anaerobic metabolism of glucose, which plays a paramount role as a signaling molecule in various steps of the cell survival. Its activity, as a master tuner of many mechanisms underlying the aging process, for example in the skin, is still presumptive, however its crucial position in the complex cross-talk between mitochondria and the process of cell survival, should suggest that l-lactate may be not a simple waste product but a fine regulator of the aging/survival ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 168 publications
(190 reference statements)
0
7
0
Order By: Relevance
“…Human facial aging is increasingly being studied; however, to our knowledge, no studies have investigated the roles of sex hormones in facial aging using GWAS data. Sex hormone levels are thought to fluctuate with age and to be associated with facial aging, and testosterone and bioavailable testosterone levels decline with age, particularly in men ( 26 ). Estradiol levels also decline with age, with a rapid decline in women after menopause ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human facial aging is increasingly being studied; however, to our knowledge, no studies have investigated the roles of sex hormones in facial aging using GWAS data. Sex hormone levels are thought to fluctuate with age and to be associated with facial aging, and testosterone and bioavailable testosterone levels decline with age, particularly in men ( 26 ). Estradiol levels also decline with age, with a rapid decline in women after menopause ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study suggested that regular exercise rejuvenated aging skin conditions 35 . A recent review highlighted that lactate acts as a signaling molecule that interacts with mitochondrial biogenesis and turnover and tunes the ability of cells to respond to stressors 36 . Therefore, these physiological adaptations in skin tissue might occur due to lactate accumulation after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The present results of skin ISF lactate dynamics in this study can provide new hypotheses. Growing evidence suggests that chronic exercise improved skin conditions (2,3), and lactate acts as a signaling molecule that interacts with mitochondrial biogenesis and turnover and tunes the ability of cells to respond to stressors (9). These findings and the present results suggest that the beneficial physiological adaptation of skin tissue to chronic exercise might be due to the accumulated effects of acute exercise-induced long-lasting lactate elevation in the skin ISF.…”
Section: Discussionmentioning
confidence: 99%
“…In aging, ozone exerts its ability in eliciting pro-survival mechanisms, which usually are induced by low doses of this compound, 23 and which may activate complex regulatory systems involving mitochondria turnover and other regulatory molecules usually associated with stress such as H 2 O 2 and lactate. 24 Most of the finesse in using ozone in the so-called "ozone therapy", 25,26 which is not a therapy but a medical adjunct treatment, lies on the physician's ability in tailoring sound and effective protocols with proper ozone dosages and sound, standardized administration routes. The purpose is to elicit the production of ROS and other mediators, such as 4-HNE, in a way able to induce their "signaling" property, rather than intrinsic toxic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In aging, ozone exerts its ability in eliciting pro-survival mechanisms, which usually are induced by low doses of this compound, 23 and which may activate complex regulatory systems involving mitochondria turnover and other regulatory molecules usually associated with stress such as H 2 O 2 and lactate. 24…”
Section: Introductionmentioning
confidence: 99%